Mapping the past: Building public knowledge places to meet community needs - McCarthy, Gavan (Circumscribere International Journal for the History of Science, 2011)
Contemporary web-based technologies have enabled torrents of information to arrive at our doorstep. Much of this information documents the here and now and most of it disappears leaving little trace. It services our need for news and may help people feel connected to the world in which they live. This knowledge of the present also synchronizes communities and creates webs of relationships critical for functional and operational effectiveness. However, it is argued, that this synchronic mapping is not sufficient to enable communities to work effectively through time. In addition to the present, communities need knowledge of their past - a diachronic mapping of what went before. These mappings provide contextual frameworks against which current and past events can be understood. They provide places where meanings can be explored and reasons discovered. Whether it is managing radioactive waste or dealing with the consequences of out-of-home care, communities need access to resilient and reliable information about their past. This paper explores the necessary conditions for building web-based long-lasting public knowledge places.